Direito à memória: modos de viver e morar em Uberlândia entre as décadas de 1960 e 1980 - Silva Júnior, Renato Jales (2013)
This dissertation is about the city of Uberlândia produced and built in different historical memory registers. From different records of residents of this city, especially the neighborhood of President Roosevelt problematized property building memories rebuilt by the government or by the press in the first decades of the twenty-first century. Followed by workers who live and places I chose one of these: the neighborhood of President Roosevelt. To problematize some notions such as social housing and poor carried a political connotation which required residents to these places and ways of life to be accepted to the dominant city. I Problematize also questioned the idea that sometimes accepts the social spaces of Uberlândia City were built by the partnership-estate and overlook the empowerment of residents. Oral narratives were important to redesign social places and question certain memories that these subjects withdrew from the active role of city builders. The dialogue with the subjects were also fundamental to the interpretation of the sources produced by the press and understand the attempt to establish certain way about living in the city and how these change over the pressure of social subjects.